Frequency of Amantadine-Resistant Influenza A Viruses during Two Seasons Featuring Cocirculation of H1N1 and H3N2 - Saito, Reiko (American Society for Microbiology, 2003)
In two influenza seasons during which H1N1 and H3N2 cocirculated, resistance was more frequent in H3N2 strains than in H1N1 strains after amantadine treatment. Predominant amino acid substitutions in M2 protein occurred at position 31 (serine to asparagine) in H3N2 strains and at position 27 (valine to alanine) in H1N1 strains.